Global poverty : deprivation, distribution, and development since the Cold War - Sumner, Andy, 1973- (Oxford University Press, 2016)
Why are some people poor? Why does absolute poverty persist despite substantial economic growth? What types of late economic development or 'catch-up' capitalism are associated with different poverty outcomes? Global Poverty addresses these apparently simple questions and the extent to which the answers may be shifting. One might expect global poverty to be focused in the world's poorest countries, usually defined as low-income countries, or least developed countries, or 'fragile states'. However, most of the world's absolute poor by monetary or multi-dimensional poverty - up to a billion people - live in growing and largely stable middle-income countries. At the same time, poverty has not fallen as much as the substantial economic growth would warrant. As a consequence, and as domestic resources have grown, much of global poverty has become less about a lack of domestic resources and more about questions of national inequality, social policy and welfare regimes, and patterns of economic development pursued.